Geochemical characteristics and groundwater quality in the Vientiane Plain, Laos - Brindha, Karthikeyan; Pavelic, Paul; Sotoukee, Touleelor; Douangsavanh, Somphasith; Elango, L. (Springer, 2017)
Groundwater from the shallow aquifers of the Vientiane Plain, Laos is used for domestic needs including to some extent for drinking and for household gardening. The objective of this study is to assess the groundwater quality for drinking and irrigation activities and to determine the processes that lead to the presence of major ions in groundwater. Twenty groundwater samples were collected from a village on the Plain in December 2014, January 2015, and May 2015, and analysed for major ions and selected suite of minor ions and heavy metals. Groundwater is largely acidic, fresh and soft in nature. Geochemistry showed dominant Ca–Mg–HCO3 and mixed Ca–Na–HCO3 groundwater. Sodium impacts the suitability of water for irrigation to some extent. Hydrogeochemical processes identified and verified through factor analysis indicate weathering, carbonate dissolution, ion exchange, and anthropogenic sources including salinisation, due to irrigation and use of fertilizers as sources for the occurrence of major ions at such concentrations in this area. Only concentrations of lead and iron were above the permissible limits with arsenic, copper, zinc, mercury, and uranium found to be within safe limits. Background sample (groundwater) collected 5 km from the study area and the bottled water sample were all within suitable limits for drinking. This study is the first to provide a local-level assessment of geochemical processes in groundwater of this area indicating that the groundwater does not pose any threat to human health if used for drinking based on major ions, minor ions and a suite heavy metals except for iron and lead.